The lncRNAs involved in regulating the RIG-I signaling pathway - Liu, Jing; Ji, Qinglu; Cheng, Feng; Chen, Dengwang; Geng, Tingting; Huang, Yueyue; Zhang, Jidong; He, Yuqi; Song, Tao (Frontiers in Cellular and Infection Microbiology, 2022)
Understanding the targets and interactions of long non-coding RNAs (lncRNAs) related to the ret-inoic acid-inducible gene-I (RIG-I) signaling pathway is essential for developing interventions, which would enable directing the host inflammatory response regulation toward protective im-munity. In the RIG-I signaling pathway, lncRNAs are involved in the important processes of ubiq-uitination, phosphorylation, and glycolysis, thus promoting the transport of the interferon regula-tory factors 3 and 7 (IRF3 and IRF7) and the nuclear factor kappa B (NF-κB) into the nucleus, and activating recruitment of type I interferons (IFN-I) and inflammatory factors to the antiviral action site. In addition, the RIG-I signaling pathway has recently been reported to contain the targets of coronavirus disease-19 (COVID-19)-related lncRNAs. The molecules in the RIG-I signaling pathway are directly regulated by the lncRNA–microRNAs (miRNAs)–messenger RNA (mRNA) axis. There-fore, targeting this axis has become a novel strategy for the diagnosis and treatment of cancer. In this paper, the studies on the regulation of the RIG-I signaling pathway by lncRNAs during viral infections and cancer are comprehensively analyzed. The aim is to provide a solid foundation of information for conducting further detailed studies on lncRNAs and RIG-I in the future and also contribute to clinical drug development.